Otolith chemistry does not just reflect environmental conditions: A meta‐analytic evaluation. Issue 3 (5th January 2018) - Izzo, Christopher; Reis‐Santos, Patrick; Gillanders, Bronwyn M
Abstract: Fish otoliths are widely used to answer biological and ecological questions related to movements and habitat use based on their chemical composition. Two fundamental assumptions underlie otoliths as environmental tracers and proxies for reconstructing exposure histories: (i) otolith chemistry reflects water chemistry, and (ii) ambient environmental conditions affect otolith element incorporation. Here, we test these assumptions for Sr and Ba through meta‐analyses. Our first meta‐analysis confirmed a correlation between concentrations of Sr:Ca and Ba:Ca in otoliths and the surrounding water, both elements displaying positive otolith–water correlations. The second meta‐analysis examined the relative influences of salinity and temperature on otolith Sr and Ba partition coefficients (an index of otolith element regulation). Our environmental effects meta‐analysis confirmed that otolith Sr and Ba are affected by temperature and salinity; however, study‐level covariates (e.g., water chemical concentrations and species ecological niche) influenced otolith element incorporation, and this varied by element. These findings confirm that even though otolith chemistry and elemental incorporation are differentially affected by environmental conditions, other factors play a decisive role. While we focused on studies that directly linked water and otolith chemistry, systematic reviews are key to further demonstrate the link between otolith chemistry and extrinsic and intrinsic factors. Ultimately, disentangling the relative effects of multiple factors on otolith chemistry and a detailed understanding of biomineralization is critical to the continued use of otoliths as natural tags for tracing fish movements and habitat use.